Asymptomatic Leukocytospermia and Assisted Reproductive Technology Outcomes: Reason for concern? - Marie-Christin Reich; Natalie Heide; Peter Humaidan; Sandro C. Esteves (International Brazilian Journal of Urology)
ABSTRACT Leukocytospermia, defined as ≥1×106 white blood cells (WBC)/ml of semen, is a condition frequently observed in infertile men. While symptomatic leukocytospermia is often associated with genital tract infections and managed accordingly, the clinical significance of asymptomatic leukocytospermia remains uncertain—particularly in the setting of Assisted Reproductive Technology (ART). Seminal leukocytes, primarily neutrophils, play a physiological role in immune surveillance and tissue homeostasis. However, when excessively activated, they may generate high levels of reactive oxygen species (ROS), contributing to oxidative stress, sperm dysfunction, and DNA damage. This narrative review critically examines whether asymptomatic leukocytospermia adversely affects ART outcomes, including fertilization, embryo development, clinical pregnancy, and live birth rates. A synthesis of current evidence—including meta-analyses and large retrospective studies—suggests that asymptomatic leukocytospermia does not negatively impact these outcomes. Moreover, standard sperm preparation techniques and the widespread use of ICSI appear to neutralize any potential deleterious effects from seminal leukocytes. Given the absence of compelling evidence supporting its harmful impact on ART success, routine treatment of asymptomatic leukocytospermia—particularly with empiric antibiotics—is not recommended. Such interventions may disturb the natural immune balance, promote antibiotic resistance, and increase healthcare burdens without demonstrable benefit. Nonetheless, selective treatment may be justified in specific scenarios, such as recurrent implantation failure or early pregnancy loss. Further research is warranted to standardize leukocyte detection methods and to clarify the role of adjunctive therapies. Until more definitive data emerge, an individualized, evidence-based approach remains the most appropriate strategy for managing asymptomatic leukocytospermia in infertile men pursuing ART.